A framework for performance optimisation at software architecture level. (2016) - Ye, Peng; Ni, You-Cong; Du, Xin; Li, Song; Xie, Da-Tong; Xiao, Ru-Liang
Architecture-based software performance optimisation can significantly not only save time but also reduce cost. A few rule-based performance optimisation approaches at software architecture level have been proposed in recent years. However, the count and the order of each rule usage in the optimisation process have not been fully considered in these approaches. Consequently, the search space for performance improvement is limited so that the optimal solution is hard to find out. Aiming at this problem, firstly, rule-based software performance optimisation is abstracted into a mathematical model called RPOM. The mathematical relation between usage of rules and optimal solution in performance improvement space is precisely characterised in the RPOM. Furthermore, we design a rule sequence execution framework named RSEF which can solve RPOM model. The result of this paper will help those rule-based software performance optimisation approaches to search the larger space in order to improve the quality of optimisation.